(untitled) (Kinesiology, 2023)
Exercise-induced hypoalgesia (EIH) is the acute pain reduction post-exercise. Typically, high-intensity and/or long-duration exercise is required to elicit EIH. Alternatively, low-load resistance exercise with blood flow restriction (LL+BFR) may elicit EIH. However, there is conflicting evidence regarding the necessary repetitions and volume load. This study evaluated EIH after 75 repetitions (1×30, 3×15) (BFR-75) and four sets to volitional failure (BFR-F) protocols. Twenty-six participants completed unilateral knee extensions at 30% of maximal strength using a BFR-75 and BFR-F protocol. Pain pressure threshold (PPT) of the rectus femoris was assessed before and after exercise. Repetitions completed, volume load, occlusion time, and PPT were analyzed. Participants completed more repetitions (91.4±30.5), volume load (5,204.9±2,367.0 Nm), and had a longer occlusion time (345.8±76.2 seconds) during BFR-F compared to BFR-75 (73.2±3.7 repetitions, 4,451.1±1,498.1 Nm, 300.5±52.2 seconds, respectively). Collapsed across sex, PPT increased from pre- (3.24±1.91 kgf) to post-exercise (3.76±2.27 kgf) for BFR-F but not for BFR-75 (3.51±1.67 to 3.68±2.04 kgf). The results indicated that BFR-F, but not BFR-75, elicited EIH, as assessed by an increase in PPT. Lower loads used during LL+BFR may be a clinically relevant alternative to high-intensity and/or long-duration exercise in populations that may not tolerate high-intensity or prolonged exercise to induce EIH. Key words: exercise-induced hypoalgesia, pain pressure threshold, blood flow restriction, muscle pain, resistance exercise, pain measurement